One-Dimensional Analysis and Modeling of the Xu 7 Engine Due to Changes in Valve Timing to Improve Engine Performance - Kamyab, Mohammad Hassan; Petrudi, Amin Moslemi; Scurtu, Ionut Cristian (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The advancement of technology and the upgrade of internal combustion engines, the need to use precision and efficiency in controlling and regulating the injection and refuelling sets of the engine has intensified. Proper adjustment of valve timing and ignition is effective in improving the performance of internal combustion engines. In this study, the one-dimensional model of the xu 7 engine was used in the GT Suite software and the effects of changing the timing of the valve on the performance of the engine were investigated. Then, by changing the range of the user’s required velocity, the appropriate valve timing was examined. By adjusting the timing of the valve, more power and torque can be obtained in the range of unusual engine velocity’s, and the efficiency of the engine can be determined in different types of uses. The extracted engine simulation results are designed for medium velocity’s.